Anatomy of a Stablecoin’s failure: The Terra-Luna case - Briola, Antonio; Vidal-Tomás, David; Wang, Yuanrong; Aste, Tomaso (Finance research letters, 2023)
We quantitatively describe the main events that led to the Terra project’s failure in May 2022. We first review, in a systematic way, news from heterogeneous social media sources; we discuss the fragility of the Terra project and its vicious dependence on the Anchor protocol. We hence identify the crash’s trigger events, analysing hourly and transaction data for Bitcoin, Luna, and TerraUSD. Finally, using state-of-the-art techniques from network science, we study the evolution of dependency structures for 61 highly capitalised cryptocurrencies during the down-market and we also highlight the absence of herding behaviour analysing cross-sectional absolute deviation of returns. •We describe the Terra project’s features and the mechanisms that led to its failure.•We use network science and herding approaches to capture dependency structures.•The vicious dependence of the Terra project on the Anchor protocol is reported.•We uncover BTC’s reference role during the first phase of the collapse.•Herding behaviour is not detected during the down market.